RE: What Is the Optimal Treatment for Liver Hydatid Cysts in Emergency and Elective Situations? - Öter, Serdar; Yalçın, Metin (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Öter S, Yalçın M. RE: What is the optimal treatment for liver hydatid cysts in emergency and elective situations? Turk J Gastroenterol. 2024;35(2):160.